Adaptive estimation for functional data: Using a framelet block‐thresholding method. Issue 1 (24th January 2022) - Cheng, Kun; Chen, Di‐Rong
Abstract : This article considers a framelet block‐thresholding method for estimating mean and covariance functions from discretely sampled noisy observations. Estimated convergence rates are established for all types of sampling schemes. In particular, the results reveal a phase transition phenomenon related to the number of observations on each curve. It is shown that the proposed procedures are adaptive in automatically adjusting the smoothness properties of the underlying mean and covariance functions. In contrast, theoretical results for other smoothing methods hold in the setting where smoothness parameters are assumed to be known, since the regularization parameters of estimators that depend on smoothness properties need to be chosen carefully. Simulation studies are provided to offer empirical support for the theoretical results. A comparison with other methods demonstrates that the proposed method outperforms in adaptivity. An application to a real dataset is also provided to illustrate the proposed estimation procedure. Résumé : Afin d'estimer des fonctions de moyenne et de covariance à partir d'observations bruitées, obtenues par échantillonnage discret, les auteurs de ce travail proposent d'utiliser une méthode de tramelettes avec un seuillage par blocs. Les taux de convergence associés sont estimés sous divers plans d'échantillonnage. Aussi, un phénomène de transition de phase lié au nombre d'observations sur chaque courbe est mis en évidence. Les procédures proposées ajustent automatiquement les paramètres de régularité des fonctions de moyenne et de covariance à l'étude, par opposition aux autres techniques de lissage qui nécessitent un effort supplémentaire pour que leurs paramètres de régularisation soient sélectionnés adéquatement, car ces derniers dépendent généralement de la régularité sous‐jacente. Finalement, des simulations numériques confirment les résultats théoriques et montrent que l'approche proposée surpasse les autres techniques de régularisation en termes d'adaptabilité. La méthode est ègalement illustrée au moyen d'une étude de cas.